The Katsina Factor in the History of Yawuri and Zuru Emirates: A Study of Katsinawa in Diaspora - Wara, Mansur Abubakar; Abdullahi, Yusuf (Journal of Applied And Theoretical Social Sciences, 2022)
Katsina was one of the earliest Hausa kingdoms whose influence was felt beyond Hausaland since the precolonial period. While Katsina served as a focal point to scores of migrants, many Katsinawa as well, due largely to trade, Islamic scholarship and circumstances of the 1804 Jihad, migrated and settled in different parts of West Africa. In the case of Yawuri and Zuru Emirates, Katsina had influenced their developments in the social, economic and political spheres. However, extensive research has not so far been conducted to unravel these developments. This study therefore, intends to examine the role of Katsinawa in diaspora with particular reference to Yawuri and Zuru Emirates of Kebbi State, Nigeria. The study has revealed the role of Katsinawa amidst non-Hausa communities. The study has utilized, primarily, oral and written sources.